1994
DOI: 10.1128/aac.38.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of 123 Xanthomonas maltophilia strains to clinafloxacin, PD 131628, PD 138312, PD 140248, ciprofloxacin, and ofloxacin

Abstract: The susceptibilities of 123 clinically isolated strains of Xanthomonas maltophilia to six fluoroquinolones (clinafloxacin, PD 131628, PD 138312, PD 140248, ciprofloxacin, and ofloxacin) were examined by microdilution MIC methodology. Clinafloxacin and PD 131628 were the most active compounds tested (MICs for 50% of the strains tested [MIC50s] of 0.5 and 1.0 ,ug/ml and MIC90s of 2.0 and 4.0 ,ug/ml, respectively). PD 138312, PD 140248, ciprofloxacin, and ofloxacin were less active, with MIC50s ranging from 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
(34 reference statements)
5
13
0
Order By: Relevance
“…On the other hand, newer quinolones such as clinafloxacin and sparfloxacin appear to be more active against the bacterium than the older agents in this class (14). It has been reported that 93% of 25 ciprofloxacin-resistant strains were susceptible to clinafloxacin (15). The present data have also shown that only 5% of S. maltophilia isolated from HD pneumonia patients were susceptible to ciprofloxacin, while 57% were susceptible to levofloxacin.There are scant reports on the effective use of the newer quinolones in clinical settings towards S. maltophilia-related infection and prospective studies are awaited in the future.…”
Section: Discussionsupporting
confidence: 49%
“…On the other hand, newer quinolones such as clinafloxacin and sparfloxacin appear to be more active against the bacterium than the older agents in this class (14). It has been reported that 93% of 25 ciprofloxacin-resistant strains were susceptible to clinafloxacin (15). The present data have also shown that only 5% of S. maltophilia isolated from HD pneumonia patients were susceptible to ciprofloxacin, while 57% were susceptible to levofloxacin.There are scant reports on the effective use of the newer quinolones in clinical settings towards S. maltophilia-related infection and prospective studies are awaited in the future.…”
Section: Discussionsupporting
confidence: 49%
“…Clinafloxacin was more than 10 times more active than ciprofloxacin against 99 strains of Stenotrophomonas maltophilia, resulting in 95% of strains being susceptible to clinafloxacin and 43% of strains being susceptible to ciprofloxacin. These results are comparable to those of previous studies (4,12).…”
supporting
confidence: 92%
“…Clinafloxacin, sparfloxacin, and PD-13 1628 are investigational fluoroquinolgnes with in vitro activity superior to that of ciprofloxacin against S. r n a l t o p h i l i~.~~~~~~~ In one series of 123 isolates, 94% were susceptible to clinafloxacin and 80% to PD-131628. 49 Breakpoints were 2 pg/ml. It is important to note that 80% of strains were resistant to ciprofloxacin (MIC > 2 pg/ml), and although MICs increased among other quinolones when isolates were ciprofloxacin resistant, 93% and 74% of strains remained susceptible to clinafloxacin and PD-131628, respectively.…”
Section: Antibiotic Combinationsmentioning
confidence: 97%